2017
DOI: 10.1007/s00438-017-1375-4
|View full text |Cite
|
Sign up to set email alerts
|

Major splice variants and multiple polyadenylation site utilization in mRNAs encoding human translation initiation factors eIF4E1 and eIF4E3 regulate the translational regulators?

Abstract: Alternative polyadenylation is an important and pervasive mechanism that generates heterogeneous 3'-termini of mRNA and is considered an important regulator of gene expression. We performed bioinformatics analyses of ESTs and the 3'-UTRs of the main transcript splice variants of the translational initiation factor eIF4E1 and its family members, eIF4E2 and eIF4E3. This systematic analysis led to the prediction of new polyadenylation signals. All identified polyadenylation sites were subsequently verified by 3'R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Curiously, the sedimentation of the faster migrating band observed on the eIF4E3 blots (*) was unaltered by Torin1 treatment, indicating that it was not recruited into an eIF4F complex. This behaviour suggests that it might be the N-terminally truncated isoform B that was reported not to interact with eIF4G (the eIF4E3 polyclonal antibody used in these studies was raised against the C-terminal region of the protein) ( 52 , 53 ). Therefore, upon mTOR inhibition the sedimentation profiles of eIF4E1 and eIF4E3 are inversed (Figure 2F and G ).…”
Section: Resultsmentioning
confidence: 96%
“…Curiously, the sedimentation of the faster migrating band observed on the eIF4E3 blots (*) was unaltered by Torin1 treatment, indicating that it was not recruited into an eIF4F complex. This behaviour suggests that it might be the N-terminally truncated isoform B that was reported not to interact with eIF4G (the eIF4E3 polyclonal antibody used in these studies was raised against the C-terminal region of the protein) ( 52 , 53 ). Therefore, upon mTOR inhibition the sedimentation profiles of eIF4E1 and eIF4E3 are inversed (Figure 2F and G ).…”
Section: Resultsmentioning
confidence: 96%
“…While the p70 S6K1 variant was found to be highly expressed in non-small cell lung cancer (NSCLC), the splice variants of aminoacyl-tRNA synthetases were observed under stress conditions and likely represent part of the cellular stress response [149,150]. Likewise, Mrvovà et al reported the identification of diverse alternatively spliced forms of eIF4E family members in acute lymphoblastic leukemia cell lines [151]. These alternatively spliced mRNAs were shown to either contain different polyadenylation sites, affecting the stability of the mRNA, or encode diverse C-termini, potentially altering the function of the protein.…”
Section: Rna Editing/splicing and Its Potential Role In Ribosome Bmentioning
confidence: 99%
“…Interestingly, although considered to regulate the nervous system directly or indirectly, EIF4E3 also has a role in the cardiovascular system. Mrvová, S and colleagues performed bioinformatics analyses of expressed sequence tags and the 3’-UTRs of the main transcript splice variants of the translational initiation factor EIF4E3 and showed that EIF4E3 mRNAs have a great potential in heavy post-transcriptional regulation [ 24 ]. EIF4E3 truncated transcript variants were mainly found in the brain.…”
Section: Discussionmentioning
confidence: 99%